WEED MANAGEMENT STUDIES IN LENTIL (LENS CULINARIS MEDIK) - Singh, DHEER; TOMAR, P.K. (Annals of Agricultural Research, 2014)
A field experiment with 8 treatments was conducted at Crop Research Center of G.B. Pant University of Agriculture & Technology, Pantnagar.Eight treatments viz. weedy check, fluchloralin @ 0.5, 1.0 kg/ha as PPI, isoproturon 0.5 and 1.0 kg/haas PE, pendimethalin 0.5 and 1.0 kg/ha as PE, hand weeding at 20 and 45 days after sowing were tested in randomized block design with three replications.Grain yield oflentil was significantly higher in two hand weeding (20 and 45 DAS) over weedy check, fluchloralin and isoproturon at both the rates of 0.5 and 1.0 kg/ha, during both the years.